Review of DC-DC boost converter derived topologies for renewable energy applications - Thulasiraman, Nivethaa; Viswanathan, Lavanya; Sriramalakshmi, Palanidoss (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper deals with three different power converter topologies for boosting the available dc input voltage. The converters considered for the study are conventional DC-DC boost converter, quasi switched boost DC-DC converter (qSBC) and quasi Z source converter (qZSC). The converters are designed for an input voltage of 24 V to deliver a power of 200 W to a resistive load. The steady-state analysis of all three topologies is discussed to determine the key characteristics of the proposed topologies. All the converters are simulated in MATLAB/Simulink environment and the outcomes are explained in detail. The performance comparison of the converters such as switch stress, diode stress and boost factor versus duty ratio are presented. Thus, this comparison helps to choose a suitable boost converter topology for a specific application.